DETERMINATION OF WATER QUALITY PARAMETERS OF KELO RIVER - Reenu Mishra, P.K.Sing, M.M.Vaishnav, Kavita Patel (Chelonian Research Foundation, 2024)
Water is a wonderful gift of nature to mankind. It has its own unique properties. It is also known as universal solvent. It is essential for all living beings. Chemically water is consisting of two part of hydrogen and one part of oxygen. Its weight is 18 .The natural water is combination of following – (1)H217O, (2) H218O (3)HD16O (4) H216O (5)HD17O(6)HD18O (7) D218O(8) D217O(9) D216O. Because both hydrogen and oxygen have isotope, so there nine combinations is possible.1 depending upon the combination of those component the properties of water vary from place to place. For example density of water varies from source to source at 40C. Type of Water Density at 40C Rain Water 9999990 Snow Water 9999977 Ocean Water 0000015 Water of crystallization in various minerals 0000024 Water of plants 0000017 River Water 0000000 Water is used for several purposes. Without water life is impossible in universe. Water is found in three different forms-solid, liquid and vapors. Our planet is known as blue planet as most of the part is covered with water, but we still face crises, becoz 97% total surface water is marine water, only 3% of it is fresh water which includes glacier also. River is one of major source of surface water. River water can be used for different purpose like drinking, irrigation, domestic use, in industry and many more. If we want to use water for any one of these purpose, we first check the water quality. Water quality is measured by various parameters. WQI is used for this purpose. On the basis of water quality parameters the degree of pollution is measured. It is also necessary to calculate parameters before using water at any purpose. In our present study we discuss the water quality parameters of Kelo River in Pree Monsoon, Monsoon & Post Monsoon. session. In present work I discuss some of them. In this study I choose kelo river water from seven different spots and analyze water quality parameters. Water is polluted by different reasons. Anthropogenic activity, Industrialization, Cultivation, Use of pesticide and fertilizers, Domestic waste, Sewage, irrigation, municipal waste etc. are responsible for aquatic pollution. Water quality parameters tell us whether the water is suitable for the purpose in which we want to use water. And it also tells us the level of pollution. KEY WORD- Aquatic pollution, WQI, Anthropogenic activity, Water pollution, Kelo River, domestic waste, Raigarh,